2004
DOI: 10.1016/j.femsle.2004.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of protease overproducing mutants of Trichoderma harzianum

Abstract: Several Trichoderma strains have been reported to be effective in controlling plant diseases, and the action of fungal hydrolytic enzymes is considered as the main mechanism involved in the antagonistic process. Strain Trichoderma harzianum T334 is a potential biocontrol agent against plant pathogenic fungi with the ability to produce low levels of proteases constitutively. To improve its fungal antagonistic capacity, mutagenetic program was undertaken for the construction of protease overproducing derivates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
(28 reference statements)
1
26
0
Order By: Relevance
“…These results suggest that mutants obtained either by chemical or UV treatments, with the exception of Th11C40.1, have improved their biocontrol activity in relation to their parental strains. The obtainment of Trichoderma mutants through different procedures has allowed the obtainment of hyperhydrolytic strains with improved biocontrol activity on R. solani (Rey et al 2001), of protease overproducing strains with improved biocontrol activity against different pathogens (Szekeres et al 2004), of salt tolerant strains for the control of F. oxysporum (Mohamed and Haggag, 2006) and of pesticide polyresistant strains (Hatvani et al 2006), thus supporting the improved biocontrol effect of some of the mutants tested in this work.…”
Section: Effectiveness Of Mutants In the Control Of R Solani In Greesupporting
confidence: 61%
“…These results suggest that mutants obtained either by chemical or UV treatments, with the exception of Th11C40.1, have improved their biocontrol activity in relation to their parental strains. The obtainment of Trichoderma mutants through different procedures has allowed the obtainment of hyperhydrolytic strains with improved biocontrol activity on R. solani (Rey et al 2001), of protease overproducing strains with improved biocontrol activity against different pathogens (Szekeres et al 2004), of salt tolerant strains for the control of F. oxysporum (Mohamed and Haggag, 2006) and of pesticide polyresistant strains (Hatvani et al 2006), thus supporting the improved biocontrol effect of some of the mutants tested in this work.…”
Section: Effectiveness Of Mutants In the Control Of R Solani In Greesupporting
confidence: 61%
“…These results are consistent with previous reports on the sensitivity of T. harzianum to UV irradiation (Paul et al 2005), and also suggest that early damage of most of the T. harzianum conidia population occurred because percent recovery did not change after the different time periods of irradiation. Other research groups have been successful in obtaining Trichoderma mutants by means of UV-mutagenesis (Szekeres et al 2004;Hatvani et al 2006); nevertheless, those UV mutants were obtained using only UV-C irradiation. Our results showed that UV-C affected differently each parental strain of T. harzianum (Th11, Th12 and Th291), because different number of new strains was recovered from each parental T. harzianum after treatment, being the new strains obtained from Th11 the most abundant.…”
Section: Discussionmentioning
confidence: 99%
“…with long exposure time to UV-C irradiation. Other authors used different experimental conditions for the obtainment of UV-C mutants from those used by Papavizas and Lewis (1983), or the used in this work: UV mutants of T. harzianum T334 were obtained after irradiation for 25-30 sec with a UV-C lamp at 23 cm distance, with 10% yield after selection using p-fluorophenylalanine (Szekeres et al 2004), or UV mutants of T. harzianum T66 and of T. atroviride T122 were obtained after irradiation for 30 sec with a UV-C lamp at 40 cm distance. This latter work included 50 µg/mL tecobunazole for selection of mutant, but no yield data was provided (Hatvani et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant growth changes were observed after day 6, when the Bio-Control Index (BCI=A/B*100.) was calculated, where A corresponds to the area of the biocontrol agent, while B is the total area covered by the biocontrol agent+ phytopathogen, adapted from Szekeres et al (20). A T. harzianum strain provided by the culture collection of Universidad de Pamplona (Colombia) was used as control.…”
Section: Molecular Marker Sequencementioning
confidence: 99%